Identification of ophiostomatalean fungi associated with Tomicus pilifer infesting Pinus koraiensis in Northeastern China - Wang, Huimin; Liu, Caixia; Yue, Fangzheng; Yan, Dong-Hui; Lu, Quan (Frontiers in Microbiology, 2022)
Ophiostomatalean fungi usually facilitate bark beetles to infest tree hosts and seriously endanger the health of coniferous forests. Tomicus pilifer Spessivtsev is a common endemic bark beetle in Asia and primarily threatens Pinus koraiensis. Tomicus species have similar morphology; however, they can be differentiated by their genetic characteristics through phylogenetic analyses. To date, the 28S rDNA sequence of T. pilifer and the diversity of ophiostomatalean fungi associated with T. pilifer have not been reported. In this study, we aimed to clarify the taxonomic status of T. pilifer and identify ophiostomatalean fungi associated with T. pilifer infesting P. koraiensis in northeastern China. In total, 315 ophiostomatalean fungal strains were isolated from 62 adults of T. pilifer and 220 tissue samples from T. pilifer galleries in Jilin Province. Thirty-five representative strains were further identified by comparing their morphological and physiological characteristics and conducting the phylogenetic analysis of ITS, ITS2-LSU, TUB2, and TEF1-α. We identified nine species of ophiostomatalean fungi belonging to four genera, which included six novel species (Ceratocystiopsis changbaiensis sp. nov., Leptographium linjiangense sp. nov., Leptographium qieshaoense sp. nov., Ophiostoma piliferi sp. nov., Ophiostoma tonghuaense sp. nov., and Ophiostoma yaluense sp. nov.), two previously described species (Graphilbum interstitiale and Ophiostoma fuscum), and one undefined specie (Ceratocystiopsis sp. 1). To the best of our knowledge, this is the first report of G. interstitiale and O. fuscum in China and the fungal diversity of ophiostomatalean in T. pilifer. The dominant species were O. piliferi and L. qieshaoense, representing 39.37% and 35.87% of the isolates, respectively. The results of this study provide valuable information on the symbiotic relationship between bark beetles and ophiostomatalean fungi.